Dichotomy of dosage compensation along the neo Z chromosome of the monarch butterfly - Gu, Liuqi (Curr Biol, 2019)
Mechanisms of sex chromosome dosage compensation (SCDC) differ strikingly among animals. In Drosophila flies, chromosome-wide transcription is doubled from the single X chromosome in hemizygous (XY) males whereas in Caenorhabditis nematodes, expression is halved for both X copies in homozygous (XX) females [1, 2]. Unlike other female-heterogametic (WZ female / ZZ male) animals, moths and butterflies exhibit sex chromosome dosage compensation patterns typically seen only in male-heterogametic species [3]. The monarch butterfly carries a newly-derived Z chromosome segment that arose from an autosomal fusion with the ancestral Z [4]. Using a highly contiguous genome assembly, we show that gene expression is balanced between sexes along the entire Z chromosome, but with distinct modes of compensation on the two segments. On the ancestral Z segment, depletion of H4K16ac corresponds to nearly halving of biallelic transcription in males, a pattern convergent to nematodes. Conversely, the newly-derived Z segment shows a Drosophila-like mode of compensation, with enriched H4K16ac levels corresponding to doubled monoallelic transcription in females. Our work reveals that, contrary to the expectation of co-opting regulatory mechanisms readily in place, the evolution of plural modes of dosage compensation is also possible along a single sex chromosome within a species.